Sensorless vector control of PMSM with non-sinusoidal flux using observer based on FEM - Oksuztepe, Eyyup; Omac, Zeki; Kurum, Hasan (Springer, 2014)
Back electromotive force method has been widely used in the position and speed sensorless control of permanent magnet synchronous motors. In this method, it is supposed that the back electromotive forces induced on the stator windings by the rotor permanent magnets are sinusoidal. This assumption causes errors in the estimation of speed and position. In this paper, an observer using the stator winding linkage flux model obtained by using finite element method for position and speed sensorless field-oriented control of permanent magnet motor is proposed. The validity of the proposed method is demonstrated using DS 1104.
Keywords: Permanent magnet synchronous motor; DSP; Sensorless control; Finite element method